Eating disorders and autism spectrum: links and risks - Carpita, Barbara; Muti, Dario; Cremone, Ivan Mirko; Fagiolini, Andrea; Dell’Osso, Liliana (CNS spectrums, 2022)
In the last decades, increasing attention has been provided to socio-cultural and neurobiological factors involved in the psychopathology of feeding and eating disorders (FED), encouraging a multifactorial approach. In this framework, several authors stressed an association between FED and other kinds of psychiatric disorders from both a psychopathological and a neurobiological point of view. In particular, many promising contributions are focusing on the possible link between FED and autism spectrum disorder (ASD). Growing interest about this association rose from the frequently reported evidence of ASD-like traits amongst FED patients and abnormal eating behaviors amongst patients with ASD. This narrative review overview aims to summarize the most relevant findings about the overlap between different kinds of FED and the autism spectrum, taking into account the most recent hypotheses about the psychopathology of both these conditions. While most of the studies focused on anorexia nervosa, both ASD and autistic traits seem to be detectable also in other kinds of FED. In addition, the recently increased interest toward a dimensional approach to psychopathology led to progressively broadening the concept of ASD, focusing on its subthreshold and gender-specific manifestations and on its link with other psychiatric conditions, including FED. Globally the studies summarized here provide further support to theoretical models featuring a neurodevelopmental approach for mental disorders. In particular, FED have been conceptualized as a possible psychopathological trajectory of a neurodevelopmental alteration, toward which female gender would act as one of many predisposing factors.